2021
DOI: 10.1177/0271678x20980296
|View full text |Cite
|
Sign up to set email alerts
|

Role of perivascular and meningeal macrophages in outcome following experimental subarachnoid hemorrhage

Abstract: The distribution and clearance of erythrocytes after subarachnoid hemorrhage (SAH) is poorly understood. We aimed to characterize the distribution of erythrocytes after SAH and the cells involved in their clearance. To visualize erythrocyte distribution, we injected fluorescently-labelled erythrocytes into the prechiasmatic cistern of mice. 10 minutes after injection, we found labelled erythrocytes in the subarachnoid space and ventricular system, and also in the perivascular spaces surrounding large penetrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…In a study investigating the contribution of meninges-located mast cells in stroke pathology, depletion of mast cells resulted in decreased levels of neuroinflammation, brain swelling, and infarct size following stroke and this was partially mediated by mast-cell derived IL-6 ( Arac et al, 2019 ; Figure 3C ). Similarly, in a sub-arachnoid hemorrhage model, depletion of macrophages in the leptomeninges and perivascular spaces surrounding large arterioles prior to injury results in improved neurological scoring and reduced levels of inflammation and neuronal cell death ( Wan et al, 2021 ).…”
Section: Meningeal Response To Injury and Diseasementioning
confidence: 99%
“…In a study investigating the contribution of meninges-located mast cells in stroke pathology, depletion of mast cells resulted in decreased levels of neuroinflammation, brain swelling, and infarct size following stroke and this was partially mediated by mast-cell derived IL-6 ( Arac et al, 2019 ; Figure 3C ). Similarly, in a sub-arachnoid hemorrhage model, depletion of macrophages in the leptomeninges and perivascular spaces surrounding large arterioles prior to injury results in improved neurological scoring and reduced levels of inflammation and neuronal cell death ( Wan et al, 2021 ).…”
Section: Meningeal Response To Injury and Diseasementioning
confidence: 99%
“…Besides, we focus on the CD47-SIRP axis of microglia in regulating erythrophagocytosis, though other CNS macrophages likely play a role in neuroinflammation. Previous studies have suggested that resident microglia rather than infiltrating macrophages are involved in neuroinflammation and blood clearance after SAH, but recent studies have shown that the immune cells of choroid plexus and meningeal/perivascular macrophages also play an important role in outcome after SAH (40,41). The exact mechanism of CNS border-associated macrophages (BAMs) remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…and chemokines (MCP-1, MIP-1β, and CCL5) acting through their receptors and various adhesion molecules expressed on the surface of endothelial cells and infiltrating leukocytes, are also targets of modulation [ 27 ]. Various cellular targets, such as depletion of neutrophils or monocytes/macrophages, also downregulate inflammation [ 28 , 29 , 30 ]. Moreover, promoting microglial M2 polarization can afford neuroprotection after SAH [ 31 ].…”
Section: Possible Novel Immune Pharmacological Approaches In Asahmentioning
confidence: 99%